Uncovering the molecular mechanism of decreasing corticosterone in Toxoplasma gondii infected rats. - Tok, Rui Shen. (2012)
Toxoplasma.gondii (T.gondii) infected males rats show increased sex appeal and lowered fear for cats as compared to controls. These behavioral manipulations aim to increase parasite’s transmission efficiency and are correlated with increasing testosterone levels and decreasing corticosterone levels respectively. This project focuses on the latter, seeks to explain the molecular mechanism of decreasing corticosterone by observing the changes in mRNA expression profile of Steroidogenic acute regulatory (StAR) protein and key adrenal steroidogenic enzymes via quantitative polymerase chain reaction. Our results suggest the existence of compensatory mechanism in infected animals, probably due to the negative feedback signal produced by low corticosterone levels. Although, our results did not elucidate the exact molecular mechanism of decreasing corticosterone production, they provided a clue that the molecular changes might occur at the post transcriptional level. In addition, interplay between the hypothalamus-pituitary-adrenal (HPA) axis and hypothalamus-pituitary-gonadal (HPG) axis was found to be involved in the compensatory mechanism observed from the results. As such, we propose that further experiments be carried out to provide a elucidate the molecular mechanism of decreasing corticosterone in T.gondii infected rats. With these experiments, we also hope to confirm our speculation of the compensatory mechanism and the link between HPA and HPG axis as suggested by our results.